2023
DOI: 10.3390/biomedicines11113063
|View full text |Cite
|
Sign up to set email alerts
|

Gut–Kidney–Heart: A Novel Trilogy

Mario Caldarelli,
Laura Franza,
Pierluigi Rio
et al.

Abstract: The microbiota represents a key factor in determining health and disease. Its role in inflammation and immunological disorders is well known, but it is also involved in several complex conditions, ranging from neurological to psychiatric, from gastrointestinal to cardiovascular diseases. It has recently been hypothesized that the gut microbiota may act as an intermediary in the close interaction between kidneys and the cardiovascular system, leading to the conceptualization of the “gut–kidney–heart” axis. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…Another possible mechanism could be increased oxidative stress. Previous studies have shown that a dysbiotic gut microbial community could contribute to gut barrier dysfunction via the chronic activation of oxidative stress pathways, as higher concentrations of oxidative metabolites in the bloodstream could disrupt the TJ structural complex by modulating the assembly, localization, expression, and function of its components [18,20,24,26,27]. Interestingly, regarding occludin, a specific pattern of expression was observed in the intestinal epithelium in patients with HF regardless of ejection fraction (EF), with a gradually increasing loss of expression from the crypt to the tip of the villi.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism could be increased oxidative stress. Previous studies have shown that a dysbiotic gut microbial community could contribute to gut barrier dysfunction via the chronic activation of oxidative stress pathways, as higher concentrations of oxidative metabolites in the bloodstream could disrupt the TJ structural complex by modulating the assembly, localization, expression, and function of its components [18,20,24,26,27]. Interestingly, regarding occludin, a specific pattern of expression was observed in the intestinal epithelium in patients with HF regardless of ejection fraction (EF), with a gradually increasing loss of expression from the crypt to the tip of the villi.…”
Section: Discussionmentioning
confidence: 99%
“…Proline-rich extensin-like receptor kinases (PERK5) are instead activated by trimethylamine N-oxide (TMAO), which is derived from the product of phosphatidylcholine, found in meat and dairy products, and has been associated with cardio-renal axis changes [20]. The gut-kidney-heart axis is also affected by P-cresol sulfate and indoxyl sulfate, which are uremic toxins whose metabolism can be modulated by the composition of GM [21]. In this case, activation of the aryl hydrocarbon receptor (AHR) expressed by various immune cells leads to an increase in reactive oxygen species (ROS) and fibrosis, as well as impaired cardiac and renal function [22].…”
Section: Cardiovascular Disease: the Role Of Microbiotamentioning
confidence: 99%